Features of legal regulation of organizational management relations in labor law - Вишновецька, Світлана Василівна; Панчишак, Романа Андріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The paper describes the organizational and administrative relations in labor law, the relevance of the study are due to the fact that it is the quality of the legal regulation of organization and management relations, optimal and adequate methods and forms of their implementation depends on the effectiveness of interaction of organizational and management relations, the impact of and work together under the stability and profitability of the operation of enterprises, institutions and organizations.The article defined the purpose and content of organizational management relations, scholars analyzed the position regarding their classification according to different criteria for certain types. Substantiates the expediency of allocation of individual relations of organizational and administrative nature which may arise between employers and individual employees in the exercise of its regulatory powers.It was concluded that the organizational and administrative relations in labor law - is regulated by rules of labor law and local regulations relations arising between employers, employees, labor groups, trade unions and associations, employers and their associations and bodies of social partnership settlement over material conditions, ensuring the right of workers to participate in managing the legal entity of collective agreements, compliance Trudeau th law. The special features of the organizational and managerial relationships that are the subject of labor law should include the following: 1) the conclusion of this relationship an individual employment agreement (contract), because no employee can be a work group; 2) current legislation provided for cases where the entrepreneur is the one person both employer and employee, ie business activity is carried out without the involvement of hired labor, and in this context, organizational management relations in this case there ; 3) the employment relationship is primary in relation to organizational and administrative relations in labor law, but underestimate the role of the latter in ensuring the rights of citizens to work is not necessary, because thanks to the organizational and administrative relations between the subjects of labor law ensured the effective management of labor processes; 4) organizational and managerial relationships arise as to a particular company, and the territorial, sectoral, national levels, through the adoption of local regulations, not inconsistent with applicable labor laws of Ukraine; 5) organizational management relations in the workplace are not identical in meaning collective labor relations, as well as covering the scope of organizational and administrative relations of individual character.